TESTIMONY WITHOUT HARM: MECHANISMS TO REDUCE THE REVITIMIZATION OF CHILDREN AND ADOLESCENTS (REMUNOM, 2024)
Violence against children and adolescents is an alarming problem, encompassing different forms of violence, whether physical, sexual or psychological. Such acts have severe consequences for minors and can cause numerous problems in the short and long term, especially regarding the way in which professionals responsible for carrying out judicial procedures treat children and adolescents. This research aims to unravel and understand the provisions of Law 13.431/2017, which seeks to avoid the re-victimization of minors in relation to the crime suffered, ensuring that the procedures bring protection to victims. Brazilian legislation has advanced considerably in ensuring the rights of children and adolescents who are victims or witnesses of violent crimes, as, over the centuries, this population has gone from irrelevant individuals to developing subjects with full protection and fundamental guarantees. The effectiveness of this law and specific legislation requires assistance from qualified interdisciplinary professionals, in order to ensure that victims and witnesses are treated with dignity and recognized as holders of fundamental rights and guarantees. This research, based on bibliographical research, examines the evolution of the rights of these individuals and the changes brought to the judicial system through laws 13.431/2017 and 14.344/2022. The need to adopt specific parameters that always aim to protect children and adolescents during procedures throughout the judicial process is highlighted, in a way that prevents the re-victimization of minors during inquiries. With this legislation, it is clear that the State was concerned with fully respecting the rights of children and adolescents, giving them a voice throughout the legal procedure, reaffirming their status as citizens in full enjoyment of their rights.